A Lewis acid β-diiminato-zinc-complex as all-rounder for co- and terpolymerisation of various epoxides with carbon dioxide. Issue 3 (17th November 2016) - Reiter, M.; Vagin, S.; Kronast, A.; Jandl, C.; Rieger, B.
Abstract : Various polycarbonates with different material properties derived from CO2 and epoxides were prepared utilising a Lewis acid β-diiminato zinc catalyst. Abstract : A β-diiminato–zinc–N(SiMe3 )2 complex (1 ) was synthesised and fully characterised, including an X-ray diffraction study. The activity of catalyst1 towards the coupling reaction of CO2 and various epoxides, including propylene oxide (PO), cyclohexene oxide (CHO), styrene oxide (SO), limonene oxide (LO), octene oxide (OO) and epichlorohydrin (ECH), was investigated. Terpolymerisation of CO2, PO and LO, as well as CO2, CHO and PO, was successfully realised, resulting in polymers with adjustable glass transition temperatures and transparencies. Reaction conditions such as temperature, pressure and catalyst concentration were varied to find the optimal reaction values, especially regarding LO/CO2 . In situ IR experiments hinted that at 60 °C and a critical LO concentration, polymerisation and depolymerisation are in an equilibrium (ceiling effect). Pressurising catalyst1 with carbon dioxide resulted in a dimeric catalyst (2 ) with a OSiMe3 group as a new initiator. Homopolymerisation of different epoxides was carried out in order to explain the reactivity concerning copolymerisation reaction of CO2 and epoxides.